Commelina catharinensis (Commelinaceae): a narrow endemic and endangered new species from Santa Catarina, southern Brazil - Hassemer, Gustavo; Ferreira, João Paulo Ramos; Funez, Luís Adriano; Medeiros, João De Deus (Phytotaxa, 2016)
This contribution presents and describes Commelina catharinensis, a new, narrow endemic species only known from two very restricted areas of coastal vegetation in Santa Catarina state, southern Brazil. Both localities where this species has been collected are currently highly threatened by both legal and illegal urban advance. The new species classifies as endangered (EN) according to the IUCN criteria. We also provide here the first identification key to the species of Commelina that occur in Santa Catarina.